Surface Plasmon Resonance (SPR)-Based Multimode Optical Fiber Sensors for Electrical Transformer Oil Aging Detection - Abd Alkareem, Mariam Jamal; Ahmed , Soudad S. (Iraqi Journal of Physics, 2023)
I In this study, optical fibers were designed and implemented as a chemical sensor based on surface plasmon resonance (SPR) to estimate the age of the oil used in electrical transformers. The study depends on the refractive indices of the oil. The sensor was created by embedding the center portion of the optical fiber in a resin block, followed by polishing, and tapering to create the optical fiber sensor. The tapering time was 50 min. The multi-mode optical fiber was coated with 60 nm thickness gold metal. The deposition length was 4 cm. The sensor’s resonance wavelength was 415 nm. The primary sensor parameters were calculated, including sensitivity (6.25), signal-to-noise ratio (2.38), figure of merit (4.88), and accuracy (3.2). In the current study, the refractive index values of sucrose and water solutions at different concentrations, which were used as a calibration method, were calculated to be (1.346, 1.359, 1.382, and 1.39). It was found that when the refractive index of the sensitive medium increases, the length of the resonant wavelength increases due to the decrease in energy.